Gambaran Tingkat Pengetahuan Dokter Umum Tentang Visum Et Repertum Di Rumah Sakit Tipe C Kota Padang - Novella, Eliza Trise; Hariyani, Insil Pendri; Zainun, Zukhri (PT. Riset Press International, 2024)
General practitioners have received knowledge on making visum et repertum during their education so they should know how to make a good quality of visum et repertum. However, not all of the general practiotioners have good knowledge about visum et repertum and are able to make a good quality of visum et repertum. This study aim to give a description about general practitioners' knowledge of visum et repertum. This study is a decriptive categoric study. The population of this study was general practiotioners who worked at Type C Hospital in Padang in 2022 consisting of 31 samples. Most of the samples were 26-35 years, female, bachelor degree, have been working for 1-5 years, had the experience in making visum et repertum, the level of knowledge of visum et repertum was stated to be sufficient. The general practitioner's knowledge of visum et repertum at Type C Hospital in Padang resulted in sufficient knowledge.